(untitled) (Praxis Educativa, 2012)
In the teaching-leaning process, it is in partial attendance to classes where there is an internal contradiction between content and the necessary didactic orientation for its assimilation on the part of the student. This contradiction has a high incidence on the conception of learning means this way of studying demands. The approach presented solves the contradiction between content and didactic orientation when considering the means through which this process is implemented. The suggested solution to the contradiction is a multimedia didactic sequence contained in an electronic book whose structure and function foster independent study in partial attendance studies.